1996
DOI: 10.1152/ajprenal.1996.271.2.f451
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of amiloride-sensitive Na+ channels by endothelin-1 in distal nephron cells

Abstract: We used patch-clamp methods to investigate the effects of basolateral endothelin-1 (ET-1) on the amiloride-sensitive Na+ channel in A6 distal nephron cells. One hundred picomolar ET-1 decreased channel activity via an increase in mean time closed (P < 0.01, n = 10). Channel inhibition by pM ET-1 was mimicked by an ET-B receptor agonist (P < 0.05, n = 7) and was prevented by ET-B antagonists (P = 0.14, n = 10) but not by an ET-A antagonist (P < 0.05, n = 4). With the inhibitory ET-B receptor blocked, higher dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
59
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 0 publications
7
59
0
Order By: Relevance
“…16 Moreover, electrophysiological study showed that picomolar concentrations of ET-1 attenuate ENaC open probability via ET B receptors in an amphibian distal nephron cell line. 17 Similar results were demonstrated in mammalian fibroblast cells by stably expressing genes for the three ENaC subunits. The inhibitory effect of ET-1 on ENaC could be completely blocked when cells were pretreated with the selective Src family kinase inhibitor, PP2.…”
supporting
confidence: 67%
“…16 Moreover, electrophysiological study showed that picomolar concentrations of ET-1 attenuate ENaC open probability via ET B receptors in an amphibian distal nephron cell line. 17 Similar results were demonstrated in mammalian fibroblast cells by stably expressing genes for the three ENaC subunits. The inhibitory effect of ET-1 on ENaC could be completely blocked when cells were pretreated with the selective Src family kinase inhibitor, PP2.…”
supporting
confidence: 67%
“…16,17 The most likely explanation for these findings is derived from previous elegant in vitro studies in distal nephron cells showing that ET-1 is capable of either inhibiting ENaC via the ET B receptor or stimulating ENaC via the ET A receptor. 18 In the present study, the SHR model of SR-SH showed a similar increase in both renal ET A and ET B receptor densities after NX-NaCl treatment and thereby maintains its ET A /ET B receptor ratio constant. In contrast, SHRSP-NX-NaCl animals exhibited a significantly more pronounced increase in ET A compared with ET B binding, which resulted in a significant increase of ET A /ET B receptor ratio in this model of SS-SH.…”
Section: Specific Role Of Et a /Et B Receptor Balancesupporting
confidence: 70%
“…9,32,33 Despite these effects, this and previous studies demonstrate that rats genetically deficient in ET B or undergoing chronic ET B blockade exhibit saltsensitive hypertension responsive to ET A blockade, suggesting that Na retention and hypertension under these conditions results not from a lack of ET B -mediated natriuresis or diuresis in the kidney but from an increase in ET A signaling. 11,15 This study goes further to demonstrate that although intrarenal ET B plays a significant role in determining BP in these animals on DNa diet, it plays a relatively minor role in determining BP in these animals on HNa diet.…”
Section: Perspectivesmentioning
confidence: 51%
“…4 Several studies demonstrate that ET B activation can inhibit the epithelial sodium channel activity. 9,10 These findings led us to hypothesize that salt-sensitive hypertension in ET B -deficient rats results from an absence of ET B -mediated inhibition of the epithelial sodium channel activity in the renal tubule. However, these rats are also sensitive of ET A blockade, suggesting that hypertension in these rats is due to increased activation of ET A .…”
mentioning
confidence: 99%